Pengembangan Media Ular Tangga Interaktif (UTANGI) Berbantuan Adobe Flash untuk Meningkatkan Hasil Belajar Siswa pada Materi Pecahan Kelas III Sekolah Dasar - Widi Astuti, Rosa; Susanta, Agus; Parmadi, Bambang (Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to develop interactive snakes and ladders game media assisted by Adobe Flash to improve student learning outcomes in fractions material for grade III in elementary schools. The type of research used in this study is development research. The subjects of the study were grade III students of SDN 07 Tebing Tinggi, Empat Lawang Regency, South Sumatra as the experimental class and control class. Data collection techniques used a needs questionnaire, response questionnaire and test. The research instrument used a needs analysis instrument, expert validation instrument, question trial instrument, product effectiveness test instrument. Data analysis in this study was carried out by analyzing expert validity data, rater agreement, instrument standardization, description of learning outcomes. Based on the results of the study, it can be concluded that the development of interactive snakes and ladders game media assisted by Adobe Flash improves student learning outcomes in fractions material developed according to the material expert validator obtained a feasibility value of 0.95, the language validator obtained a feasibility value of 0.93 and the media validator obtained a feasibility value of 0.84. This media is declared very valid or feasible to be used in the learning process. From the posttest results of grade III students of SD Negeri 07 Tebing Tinggi, it is known that they obtained scores above the KKM through the use of interactive snakes and ladders game media assisted by Adobe Flash with a sig value of 0.200 > 0.05, this providing a positive impact on students towards improving student learning outcomes.